Meditation-induced changes in high-frequency heart rate variability predict smoking outcomes - Libby, Daniel J.; Worhunsky, Patrick D.; Pilver, Corey E.; Brewer, Judson A. (Frontiers in Human Neuroscience, 2012)
Background: High-frequency heart rate variability (HF-HRV) is a measure of parasympathetic nervous system output that has been associated with enhanced self-regulation. Low resting levels of HF-HRV are associated with nicotine dependence and blunted stress-related changes in HF-HRV are associated with decreased ability to resist smoking. Meditation has been shown to increase HF-HRV. However, it is unknown whether tonic levels of HF-HRV or acute changes in HF-HRV during meditation predict treatment responses in addictive behaviors such as smoking cessation. Purpose: To investigate the relationship between HF-HRV and subsequent smoking outcomes. Methods: HF-HRV during resting baseline and during mindfulness meditation was measured within two weeks of completing a 4-week smoking cessation intervention in a sample of 31 community participants. Self-report measures of smoking were obtained at a follow up 17-weeks after the initiation of treatment. Results: Regression analyses indicated that individuals exhibiting acute increases in HF-HRV from resting baseline to meditation smoked fewer cigarettes at follow-up than those who exhibited acute decreases in HF-HRV (b=-4.94, p=.009). Conclusion: Acute changes in HF-HRV in response to meditation may be a useful tool to predict smoking cessation treatment response.